2022
DOI: 10.1002/slct.202202410
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Based Formulations Intended as Protective Spray for Mask Surfaces in Prevention of Coronavirus Dissemination

Abstract: The extraordinary occurrence of COVID-19 by the fast expansion of viral infections has propelled particular interest in developing novel antiviral and virucidal agents to guarantee personal security. The main objective of this work is to propose novel formulations able to optimize the use of personal protection elements. In recent years, chitosan (CH) has attracted attention for being an interesting multifunctional, biodegradable, non-antigenic, non-toxic, and biocompatible natural polymer with antimicrobial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Compared to synthetic electrets, naturally charged polymers are most promising for long-lasting air filtration, as they can achieve high electrostatic adsorption without recharging and regeneration. Chitosan is a charged natural polymer with promise for long-lasting air filtration. Chitosan comprises N -acetyl- d -glucosamine and β-(1–4)-linked d -glucosamine with a highly stable distribution of naturally positively charged groups on its backbone. The ionizable amino and hydroxyl groups of chitosan facilitate the binding of negatively charged particles in the air and can improve the filtration efficiency of chitosan-based filters. Moreover, the positive charge of chitosan interacts with the envelope proteins of viruses, disrupts viruses’ structure, or interferes with their replication. For example, Hathout and Kassem suggested that the application of positively charged chitosan or poly- l -lysine fibers in personal protective masks or protective clothing could reduce the viral load by exploiting the electrostatic repulsion between the fibers and SARS-CoV-2 (Figure c) . Recently, Zhang et al used hot air chitosan fibers as an antiviral layer for masks, and the chitosan fibers’ electrostatic effect reduced the activity of enterovirus 71 (EV71, which can be transmitted through the respiratory tract) .…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%
“…Compared to synthetic electrets, naturally charged polymers are most promising for long-lasting air filtration, as they can achieve high electrostatic adsorption without recharging and regeneration. Chitosan is a charged natural polymer with promise for long-lasting air filtration. Chitosan comprises N -acetyl- d -glucosamine and β-(1–4)-linked d -glucosamine with a highly stable distribution of naturally positively charged groups on its backbone. The ionizable amino and hydroxyl groups of chitosan facilitate the binding of negatively charged particles in the air and can improve the filtration efficiency of chitosan-based filters. Moreover, the positive charge of chitosan interacts with the envelope proteins of viruses, disrupts viruses’ structure, or interferes with their replication. For example, Hathout and Kassem suggested that the application of positively charged chitosan or poly- l -lysine fibers in personal protective masks or protective clothing could reduce the viral load by exploiting the electrostatic repulsion between the fibers and SARS-CoV-2 (Figure c) . Recently, Zhang et al used hot air chitosan fibers as an antiviral layer for masks, and the chitosan fibers’ electrostatic effect reduced the activity of enterovirus 71 (EV71, which can be transmitted through the respiratory tract) .…”
Section: Electroactive Materials For Preventing Virus Infections In F...mentioning
confidence: 99%